2019
DOI: 10.1111/acer.14253
|View full text |Cite
|
Sign up to set email alerts
|

A Rationale for Allopregnanolone Treatment of Alcohol Use Disorders: Basic and Clinical Studies

Abstract: For many years, research from around the world has suggested that the neuroactive steroid (3a,5a)-3hydroxypregnan-20-one (allopregnanolone or 3a,5a-THP) may have therapeutic potential for treatment of various symptoms of alcohol use disorders (AUDs). In this critical review, we systematically address all the evidence that supports such a suggestion, delineate the etiologies of AUDs that are addressed by treatment with allopregnanolone or its precursor pregnenolone, and the rationale for treatment of various co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 215 publications
(278 reference statements)
0
26
0
Order By: Relevance
“…In summary, the ability of 3α,5α-THP to inhibit MyD88-dependent TLR signals suggests a wide applicability to many inflammatory conditions that involve TLR activation of pro-inflammatory pathways 27 , 28 , 31 . Since neurosteroids, like immune factors, circulate in the bloodstream, cross the blood brain barrier, diffuse between different cell types, and exhibit paracrine effects in many cells, it is likely that neurosteroids are endogenous modulators of TLR activation and may contribute to inflammatory disease susceptibility and recovery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In summary, the ability of 3α,5α-THP to inhibit MyD88-dependent TLR signals suggests a wide applicability to many inflammatory conditions that involve TLR activation of pro-inflammatory pathways 27 , 28 , 31 . Since neurosteroids, like immune factors, circulate in the bloodstream, cross the blood brain barrier, diffuse between different cell types, and exhibit paracrine effects in many cells, it is likely that neurosteroids are endogenous modulators of TLR activation and may contribute to inflammatory disease susceptibility and recovery.…”
Section: Discussionmentioning
confidence: 97%
“…It acts upon synaptic and extrasynaptic γ-aminobutyric acid type A (GABA A ) receptors to mediate phasic and tonic inhibition 19 , 20 , has anesthetic, anticonvulsant, sedative, and anxiolytic effects 21 , and modulates the hypothalamic pituitary adrenal axis to reduce stress activation 22 . Significantly, 3α,5α-THP and/or its precursors progesterone and pregnenolone, were shown to be effective in clinical studies of traumatic brain injury 23 , schizophrenia 24 , cocaine craving 25 , and post-partum depression 26 , identifying them as promising therapeutics 27 , 28 . Remarkably, these diverse conditions all exhibit pro-inflammatory immune and neuroimmune activation.…”
Section: Introductionmentioning
confidence: 99%
“…These maturational changes are susceptible to exposure to alcohol or stress during this period, with behavioral and structural changes often becoming permanent. Promising targets for future research may include populations of GABAergic neurons, as alcohol and stress both impact this system ( Morrow et al, 2020 ; Woodward and Coutellier, 2021 ). Further investigation into behavioral effects of adolescent alcohol or stress may uncover potential factors influencing individual sensitivity to these insults, as there is often variability in outcomes in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of neuroactive steroids has reduced voluntary alcohol consumption in male rats exposed to ethanol during adolescence ( Gurkovskaya et al, 2009 ). Because of this demonstrated effect, neuroactive steroids have emerged as a potential treatment strategy for AUD ( Morrow et al, 2020 ); however, studies testing the efficacy of neuroactive steroids across sex and broader age ranges are limited.…”
Section: Animal Studies Of Alcohol Exposurementioning
confidence: 99%
“…Since acute alcohol stimulates neurosteroidogenesis ( Korpi et al, 2001 ; Khisti et al, 2002 ), the dampened response we observed after long-term chronic alcohol consumption may be related to an adaptive mechanism leading to alcohol dependence. This may provide a rationale for the use of synthetic neurosteroids (e.g., allopregnanolone) in the treatment of AUD ( Morrow et al, 2020 ). Our previous work showed similar effects in the hippocampus of rats exposed to chronic intermittent ethanol administration ( Cagetti et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%